1974
DOI: 10.1111/j.1432-1033.1974.tb03251.x
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Amino‐Acid Sequence of Non‐Immunolobulin Amyloid Fibril Protein AS in Rheumatoid Arthritis

Abstract: The primary structure of a non-immunoglobulin amyloid protein AS has been determined.The protein was found to consist of 76 amino acid residues corresponding to a molecular weight of 9145. The sequence analysis showed clearly that the protein was homogeneous. A characteristic distribution of hydrophobic amino acids was observed and suggested as being of importance for the ability of this protein to form fibrils. A comparison of the protein with other amyloid protein AS showed a high degree of variability, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(96 citation statements)
references
References 25 publications
1
94
1
Order By: Relevance
“…Levin et al (10) suggested that protein AS is a fragment of a larger protein, since the N-terminal part of the protein in their experiments seemed to be heterogenous. We have, however, found only one amino acid, arginine, in the N-terminal position of protein AS of a secondary amyloid previously described (8,20). However, this doegs not rule out the hypothesis that protein AS is a fragment, a degradation product or a subunit of protein ASC.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…Levin et al (10) suggested that protein AS is a fragment of a larger protein, since the N-terminal part of the protein in their experiments seemed to be heterogenous. We have, however, found only one amino acid, arginine, in the N-terminal position of protein AS of a secondary amyloid previously described (8,20). However, this doegs not rule out the hypothesis that protein AS is a fragment, a degradation product or a subunit of protein ASC.…”
Section: Resultsmentioning
confidence: 50%
“…The molecular weight of protein ASC (100,000) is far higher than that of protein AS (9,145) as determined by the total amino acid sequence (20). Levin et al (10) suggested that protein AS is a fragment of a larger protein, since the N-terminal part of the protein in their experiments seemed to be heterogenous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyphens denote gaps to optimize homology; <Q symbolizes a pyrollidone carboxyl residue. An asterisk indicates the C-terminus of the deposited fibrillar form in man [19,20]. Sequences have been determined on the protein unless noted otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…In certain species, it is either genetically determined or an idiopathic variety (Benditt and Eriksen, 1973; for review, see Glenner, 1980). Protein AA has been identified in various species including man (Benditt and Eriksen, 1973;Ein, Kimura, Terry, Magnotta and Glenner, 1972;Levin, Franklin and Frangione, 1972;Sletten and Husby, 1974), monkey (Benditt and Eriksen, 1973;Doepel, Glorioso, Newcomer, Skinner and Abrams, 1981;Hermodson, Kuhn, Walsh, Neurath, Eriksen and Benditt, 1972), mouse (Eriksen, Ericsson, Pearsall, Lagunoff and Benditt, 1976;Skinner, Shirahama, *8bbreuiatzons: AA :…”
Section: Introductionmentioning
confidence: 99%